PENINGKATAN KUALIFIKASI PROFESI BAGI GURU BAHASA JERMAN SE-MALANG RAYA - Kharis, M.; Syafruddin, Dudy (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
The training of MOOC-based learning aims to improve the academicqualifications for German language teachers in Malang. The methods wereseminar and demonstration, which demonstrate the operation of the MOOC.Through this activity, the teachers said, that MOOC courses can help them toimprove their skills of the German language